List ks. Tadeusza STYCZNIA do Jego Magnificencji ks. prof. dr. hab. Andrzeja Szostka, Rektora KUL, w sprawie odmowy przyjęcia Krzyża Kawalerskiego Orderu Odrodzenia Polski od prezydenta Aleksandra Kwaśniewskiego (Lublin, 9 X 2000) - STYCZEŃ, Tadeusz (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
In his letter to Fr. Prof. Andrzej Szostek, Rector of the Catholic University of Lublin, Fr. Tadeusz Styczeń refuses to accept the Officer’s Cross of the Order of Polonia Restituta from Mr. Aleksander Kwaśniewski, President of the Republic of Poland, in order to demonstrate his solidarity with the unborn, whose right to life was questioned in the amendment to the existing law on abortion approved of by Mr. Aleksander Kwaśniewski.